Cooperative treatment method for shale gas development high-salt organic wastewater

Through multi-process synergistic treatment methods, including coagulation precipitation, electrochemical catalytic oxidation, reverse osmosis and low-temperature MVR evaporation, the problem of high-salt organic wastewater treatment of shale gas development is solved, efficient wastewater treatment and salt resources are achieved, and strict emission standards are met.

CN119874112APending Publication Date: 2025-04-25CHONGQING INST OF GEOLOGY & MINERAL RESOURCES +2

Patent Information

Application Number
CN202510260766.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The high-salt organic wastewater generated during shale gas development is difficult to treat, and the existing technology cannot effectively realize the low-carbon, economical and efficient treatment of wastewater and the comprehensive utilization of salt resources.

Method used

Multi-process synergistic treatment methods are adopted, including integrated coagulation and precipitation treatment, electrochemical catalytic oxidation and bursting of the microscope, two-stage reverse osmosis gradient desalination and low-temperature MVR evaporation-crystal form regulation. By optimizing the process parameters of each treatment unit, efficient removal of pollutants and resource utilization of salt are achieved.

Benefits of technology

The low-carbon, economical and efficient treatment of high-salt organic wastewater has been achieved. The effluent water quality meets the requirements of the "Sichuan Province Shale Gas Mining Water Pollutant Emission Standards", and the salt resources are comprehensively utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874112A_ABST
    Figure CN119874112A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high-salt organic wastewater treatment, and particularly relates to a shale gas development high-salt organic wastewater co-treatment method, which comprises treatment units such as coagulation and precipitation integration, electrochemical catalytic oxidation complex breaking, two-stage reverse osmosis gradient desalination, low-temperature MVR evaporation-crystal form regulation and control and the like. The method provided by the invention can realize optimized coupling of process parameters of each treatment unit and high-efficiency collaboration of material flow / energy flow, and realizes low-carbon, economic and high-efficiency standard treatment of shale gas high-salt organic wastewater and resource comprehensive utilization of crystalline salt; and the quality of the treated effluent meets the direct emission limit value requirement in table 1 in Discharge Standard of Water Pollutants for Shale Gas Exploitation in Sichuan Province (DB51 / 3203-2024). The method is also suitable for treating shale gas production wastewater with similar water quality characteristics, and has good popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-salt organic wastewater treatment, and in particular to a method for collaboratively treating high-salt organic wastewater in shale gas development. Background Art

[0002] my country has achieved large-scale development and utilization of shale gas resources. In 2024, shale gas production will reach more than 25 billion cubic meters. Four national shale gas demonstration areas have been built, including Chongqing Fuling, Sichuan Weiyuan-Changning, Yunnan-Guizhou Zhaotong, and Yanchang Petroleum Yan'an. At present, efforts are being made to build a national natural gas (shale gas) production capacity base of 100 billion cubic meters in the Sichuan-Chongqing region to ensure national energy and resource security. The successful exploitation of shale gas requires large-scale hydraulic fracturing operations, during which a large amount of fracturing flowback wastewater will be generated. This type of wastewater has the characteristics of large differences in water volume (the proportion of flowback volume to fracturing fluid ranges from 5% to 30% on average), high salinity, complex pollutant components, high concentration of organic pollutants, poor biodegradability, and difficulty in treatment, and the emission standards are not unified. At present, except for a very small number of shale gas fields that have built desalination treatment facilities (involving ultrafiltration + reverse osmosis + MVR, four-effect evaporation, electrodialysis + MBR + reverse osmosis + multi-effect evaporation crystallization and other processes), other shale gas fields (blocks) fracturing return wastewater is mainly transported to surrounding towns or industrial sewage treatment plants by tank trucks after pre-treatment and further treated to meet the sewage treatment plant emission standards before being discharged into natural water bodies, which increases the treatment load of sewage treatment plants and brings challenges to ecological and environmental supervision.

[0003] In order to strengthen the management of shale gas fracturing flowback wastewater treatment, Sichuan and Chongqing have jointly formulated a unified standard for shale gas extraction water pollutant emission standards (mandatory standards). The Sichuan Provincial Standard was released in December 2024, and the Chongqing Municipal Standard is planned to be released in March 2025 and will be implemented on July 1, 2025. The standard involves 21 indicators such as chemical oxygen demand (CODCr), fluoride, chloride, total dissolved solids (TDS), boron, and soluble barium, which put forward new requirements for the treatment of shale gas fracturing flowback wastewater.

[0004] Therefore, it is urgent to develop a method for the coordinated treatment of high-salt organic wastewater in shale gas development to achieve low-carbon, economical and efficient treatment of wastewater. Summary of the invention

[0005] In response to the above-mentioned key technical issues, the present invention provides a method for the coordinated treatment of high-salt organic wastewater in shale gas development. By optimizing the process parameters of each treatment unit and the synergistic effect, the overall degradation and removal efficiency of pollutants is improved, and the efficient resource utilization of evaporated crystallized salt and the harmless treatment of wastewater to meet discharge standards are achieved.

[0006] The purpose of the present invention is achieved by the following technical solutions: A method for collaboratively treating high-salinity organic wastewater in shale gas development, characterized in that it comprises the following steps: (1) Integrated coagulation and sedimentation treatment (S1) The high-salinity organic wastewater from shale gas development with influent CODCr 1000±500mg / L, ammonia nitrogen 52±8mg / L, TOC 980±220mg / L, chloride 21580±1500mg / L, TDS 54280±4000mg / L was treated in the following order: ① Microfiltration pretreatment: using α-Al2O3 ceramic microfiltration membrane (pore size 0.20-0.25μm), controlling the transmembrane pressure difference to 0.18-0.22MPa, membrane surface flow rate to 3.0-3.5m / s, synchronously adding HEDP 2.0-3.0mg / L and PESA 0.5-1.5mg / L (mass ratio 2:1±0.3), scale inhibition efficiency ≥90% (CaCO3 scaling rate ≤0.05g / (m²·h)); ② Coagulation reaction: add PAC 50-300mg / L, CPAM 2-15mg / L (cationic degree ≥50%, intrinsic viscosity ≥4.0dL / g), stir at gradient speed in stages (paddle diameter / pool diameter ratio 1:3-1:5, G value control of 400-600 s⁻¹ in fast stage, corresponding speed 120-150 rpm, reaction time 2±1min, G value control of 30-50 s⁻¹ in slow stage, corresponding speed 40-60rpm, reaction time 15±5min), adjust pH to 6.5-7.0 (0.5mol / L NaHCO3 linkage control, response time ≤20s); ③ Inclined plate sedimentation: using reinforced polypropylene inclined plate (inclination angle 55-60°, bending strength ≥ 60MPa), surface load ≤ 0.8m³ / (m²·h), supporting ultrasonic sludge concentration (28±2kHz, power density 0.6-0.8W / L), sludge moisture content is reduced from 99% to 95-97%; ④ Stability control: When |Zeta potential| < 30mV, automatically add PAC 0.5-1.0mg / L (Al2O3 ≥ 28%) and start alkaline washing (0.1mol / L NaOH 30s → water washing 20s) to make the suspended solids in the effluent ≤ 10mg / L and |Zeta potential| ≥ 30mV; (2) Electrochemical catalytic oxidation complex breaking (S2) The treated water in step S1 enters the electrochemical reactor and uses a titanium-based ruthenium-iridium anode (coating 3.2-3.8μm (uniformity ≤±5%), oxygen vacancies ≥1×10¹ 8 / cm³) and graphite cathode, control the current density to 35-45mA / cm² (voltage to 4.5-5.2V), plate spacing to 7±0.5mm, flow rate to 1.0±0.1m / s, time to 45-50min, and simultaneously add K2S2O8 0.15-0.25mmol / L (increase by 0.05mmol / L / time during mother liquor circulation), so that CODCr removal rate ≥70%, TOC ≥60% (current efficiency ≥85%); (3) Two-stage reverse osmosis gradient desalination (S3) The treated water in step S2 enters a two-stage reverse osmosis desalination device in series. The first-stage reverse osmosis adopts an anti-pollution polyamide membrane (molecular weight cutoff 280±20Da), an operating pressure of 2.8-3.1MPa, a pH of 6.5-7.0, a CODCr retention rate ≥95% (SDI≤3.0), and a water production flux ≥20L / (m²·h); the second-stage reverse osmosis adopts a polypiperazineamide seawater desalination membrane (operating pressure 5.0±0.2MPa), a Cl⁻ retention rate ≥99.8%, and a water production flux of 0.60±0.03 times that of the first stage; Water production indicators: CODCr<35mg / L, ammonia nitrogen<2.5mg / L, TOC<10mg / L, chloride<700mg / L, TDS<1300mg / L (in compliance with DB51 / 3203-2024); (4) Low temperature MVR evaporation-crystal form control (S4) In step S3, the concentrated water enters the MVR treatment system, controls the evaporation chamber to 50-55°C (vacuum degree -0.090±0.002MPa), the compressor compression ratio to 1:3.1±0.05 (specific energy consumption ≤25kWh / ton of water), ultrasonic anti-scaling (35±1kHz, power density 0.8±0.1W / L), and produces NaCl crystals (D50 200±10μm, purity ≥99.2%, water content ≤0.4%); when the mother liquor TDS ≤210000mg / L and SO4²⁻ ≤350mg / L, circulate to S2 for treatment (cycle ≤2 times, TOC increase ≤10%).

[0007] In step S1, the microfiltration membrane flux attenuation rate is ≤3% / 24h (chemical cleaning cycle ≥72h), the coagulation pH fluctuation is ≤±0.2 (calibration frequency ≥1 time / 4h), and the sludge volume reduction rate is ≥40%.

[0008] In step S2, the titanium-based ruthenium-iridium electrode is prepared by magnetron sputtering, with a sputtering power of 200-250 W, Ar 50-80 sccm, a substrate temperature of 300-350° C., a Ru / Ir molar ratio of 7.5:2.5±0.2 (composition deviation ≤±0.3at%), and an accelerated life of ≥6200 h (a cell voltage increase of ≥15% is a failure standard).

[0009] In step S3, the first-level membrane has a retention rate of ≥98% for benzene series (tested for 24 hours), the second-level membrane has a Cl⁻ / Na⁺ selectivity coefficient of ≥1.05 (NaCl 5000±200mg / L), and the pH control response is ≤30s (calibration frequency ≥1 time / 8h).

[0010] In step S4, PASP (terminal carboxyl group ≥ 85%) was compounded with polyether-modified siloxane (4:1 ± 0.5), the crystal sphericity was ≥ 0.85 (100 samples were analyzed by ImageJ), and the mother liquor circulation flow rate accounted for ≤ 15%.

[0011] The preparation of the TiO2 / nitrogen-doped graphene catalyst in step S2 includes: hydrothermal synthesis of nitrogen-doped graphene carrier (C / N 1:1.1-1.3, nitrogen content 7.5-10.5at%, specific surface area 900-1100m² / g); ALD deposition of TiO2 (220±5°C, 55-58 cycles), thickness 2-3nm (anatase phase ≥93%); catalyst surface hydroxyl density 4.8-5.2 / nm², fluorescence lifetime ≥15ns; TOC removal rate decay ≤5% (specific surface area loss ≤8%) after 10 cycles; the catalyst has a two-dimensional layered heterojunction (interface charge transfer resistance ≤50Ω·cm²), XRD 2θ=25.3±0.2° (half peak width ≤0.3°).

[0012] The beneficial effects of the present invention are: The present invention provides a method for treating high-salinity organic wastewater from shale gas development by using multiple processes such as electrochemical catalytic oxidation, multi-stage reverse osmosis, and low-temperature MVR evaporation and crystallization. The method can achieve the optimized coupling of process parameters of each treatment unit and the efficient coordination of material flow / energy flow, and realize the low-carbon, economical, and efficient treatment of high-salinity organic wastewater and the comprehensive resource utilization of crystallized salt. The chemical oxygen demand (COD Cr ), ammonia nitrogen (measured in N), total organic carbon (TOC), chlorides, total dissolved solids (TDS) and other indicators all meet the direct emission limit requirements of Table 1 in the "Sichuan Shale Gas Production Water Pollutant Emission Standard" (DB51 / 3203-2024); the present invention is also suitable for treating shale gas production wastewater with similar water quality characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Process flow diagram for developing a co-treatment method for high-salinity organic wastewater for a shale gas. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is: a method for collaboratively treating high-salt organic wastewater in shale gas development, comprising the following steps: (1) Integrated coagulation and sedimentation treatment (S1) The high-salinity organic wastewater from shale gas development with influent CODCr 1000±500mg / L, ammonia nitrogen 52±8mg / L, TOC 980±220mg / L, chloride 21580±1500mg / L, TDS 54280±4000mg / L was treated in the following order: ① Microfiltration pretreatment: using α-Al2O3 ceramic microfiltration membrane (pore size 0.20-0.25μm), controlling the transmembrane pressure difference to 0.18-0.22MPa, membrane surface flow rate to 3.0-3.5m / s, synchronously adding HEDP 2.0-3.0mg / L and PESA 0.5-1.5mg / L (mass ratio 2:1±0.3), scale inhibition efficiency ≥90% (CaCO3 scaling rate ≤0.05g / (m²·h)); ② Coagulation reaction: add PAC 50-300mg / L, CPAM 2-15mg / L (cationic degree ≥50%, intrinsic viscosity ≥4.0dL / g), stir at gradient speed in stages (paddle diameter / pool diameter ratio 1:3-1:5, G value control of 400-600 s⁻¹ in fast stage, corresponding speed 120-150 rpm, reaction time 2±1min, G value control of 30-50 s⁻¹ in slow stage, corresponding speed 40-60rpm, reaction time 15±5min), adjust pH to 6.5-7.0 (0.5mol / L NaHCO3 linkage control, response time ≤20s); ③ Inclined plate sedimentation: using reinforced polypropylene inclined plate (inclination angle 55-60°, bending strength ≥ 60MPa), surface load ≤ 0.8m³ / (m²·h), supporting ultrasonic sludge concentration (28±2kHz, power density 0.6-0.8W / L), sludge moisture content is reduced from 99% to 95-97%; ④ Stability control: When |Zeta potential| < 30mV, automatically add PAC 0.5-1.0mg / L (Al2O3 ≥ 28%) and start alkaline washing (0.1mol / L NaOH 30s → water washing 20s) to make the suspended solids in the effluent ≤ 10mg / L and |Zeta potential| ≥ 30mV; (2) Electrochemical catalytic oxidation complex breaking (S2) The treated water in step S1 enters the electrochemical reactor and uses a titanium-based ruthenium-iridium anode (coating 3.2-3.8μm (uniformity ≤±5%), oxygen vacancies ≥1×10¹ 8 / cm³) and graphite cathode, control the current density to 35-45mA / cm² (voltage to 4.5-5.2V), plate spacing to 7±0.5mm, flow rate to 1.0±0.1m / s, time to 45-50min, and simultaneously add K2S2O8 0.15-0.25mmol / L (increase by 0.05mmol / L / time during mother liquor circulation), so that CODCr removal rate ≥70%, TOC ≥60% (current efficiency ≥85%); (3) Two-stage reverse osmosis gradient desalination (S3) The treated water in step S2 enters a two-stage reverse osmosis desalination device in series. The first-stage reverse osmosis adopts an anti-pollution polyamide membrane (molecular weight cutoff 280±20Da), an operating pressure of 2.8-3.1MPa, a pH of 6.5-7.0, a CODCr retention rate ≥95% (SDI≤3.0), and a water production flux ≥20L / (m²·h); the second-stage reverse osmosis adopts a polypiperazineamide seawater desalination membrane (operating pressure 5.0±0.2MPa), a Cl⁻ retention rate ≥99.8%, and a water production flux of 0.60±0.03 times that of the first stage; Water production indicators: CODCr<35mg / L, ammonia nitrogen<2.5mg / L, TOC<10mg / L, chloride<700mg / L, TDS<1300mg / L (in compliance with DB51 / 3203-2024); (4) Low temperature MVR evaporation-crystal form control (S4) In step S3, the concentrated water enters the MVR treatment system, controls the evaporation chamber to 50-55°C (vacuum degree -0.090±0.002MPa), the compressor compression ratio to 1:3.1±0.05 (specific energy consumption ≤25kWh / ton of water), ultrasonic anti-scaling (35±1kHz, power density 0.8±0.1W / L), and produces NaCl crystals (D50 200±10μm, purity ≥99.2%, water content ≤0.4%); when the mother liquor TDS ≤210000mg / L and SO4²⁻ ≤350mg / L, circulate to S2 for treatment (cycle ≤2 times, TOC increase ≤10%).

[0015] In step S1, the microfiltration membrane flux attenuation rate is ≤3% / 24h (chemical cleaning cycle ≥72h), the coagulation pH fluctuation is ≤±0.2 (calibration frequency ≥1 time / 4h), and the sludge volume reduction rate is ≥40%.

[0016] In step S2, the titanium-based ruthenium-iridium electrode is prepared by magnetron sputtering, with a sputtering power of 200-250 W, Ar 50-80 sccm, a substrate temperature of 300-350° C., a Ru / Ir molar ratio of 7.5:2.5±0.2 (composition deviation ≤±0.3at%), and an accelerated life of ≥6200 h (a cell voltage increase of ≥15% is a failure standard).

[0017] In step S3, the first-level membrane has a retention rate of ≥98% for benzene series (tested for 24 hours), the second-level membrane has a Cl⁻ / Na⁺ selectivity coefficient of ≥1.05 (NaCl 5000±200mg / L), and the pH control response is ≤30s (calibration frequency ≥1 time / 8h).

[0018] In step S4, PASP (terminal carboxyl group ≥ 85%) was compounded with polyether-modified siloxane (4:1 ± 0.5), the crystal sphericity was ≥ 0.85 (100 samples were analyzed by ImageJ), and the mother liquor circulation flow rate accounted for ≤ 15%.

[0019] The preparation of the TiO2 / nitrogen-doped graphene catalyst in step S2 includes: hydrothermal synthesis of nitrogen-doped graphene carrier (C / N 1:1.1-1.3, nitrogen content 7.5-10.5at%, specific surface area 900-1100m² / g); ALD deposition of TiO2 (220±5°C, 55-58 cycles), thickness 2-3nm (anatase phase ≥93%); catalyst surface hydroxyl density 4.8-5.2 / nm², fluorescence lifetime ≥15ns; TOC removal rate decay ≤5% (specific surface area loss ≤8%) after 10 cycles; the catalyst has a two-dimensional layered heterojunction (interface charge transfer resistance ≤50Ω·cm²), XRD 2θ=25.3±0.2° (half peak width ≤0.3°).

[0020] The present invention is further described in conjunction with the following examples, but the present invention is not limited to the examples.

[0021] Example 1: This example treats shale gas fracturing flowback wastewater with an influent quality of CODCr 980 mg / L, ammonia nitrogen 50 mg / L, TOC 960 mg / L, chloride 21000 mg / L, and TDS 54000 mg / L, including the following treatment steps: (1) Integrated coagulation and sedimentation treatment (S1) ① Microfiltration pretreatment: using α-Al2O3 ceramic microfiltration membrane (pore size 0.20μm), transmembrane pressure difference 0.20MPa, membrane surface flow rate 3.2m / s, synchronous addition of HEDP 2.5mg / L and PESA 1.0mg / L (mass ratio 2:1); ② Coagulation reaction: Add PAC 120mg / L, CPAM 5mg / L (cationic degree 55%, intrinsic viscosity 4.2dL / g), rapid stirring stage G value 400-600s -1 (135rpm), maintain for 2min, slow stage G value 30-50s -1 (50 rpm), maintained for 15 min, the ratio of stirring blade diameter to cell body diameter was 1:3, and the pH was adjusted to 6.8 (response time 18 s); ③ Inclined plate sedimentation: The inclination angle of the reinforced polypropylene inclined plate is 58°, the surface load is 0.7m³ / (m²·h), the ultrasonic sludge concentration power density is 0.7W / L, and the sludge moisture content is reduced from 99% to 96%; ④ Stability control: After automatically adding PAC 0.8mg / L (Al2O330%), the |Zeta potential| increased from 28mV to 32mV (in line with the colloid stability criterion: log([PAC])=0.05×Δ|Zeta|+log([SS]0 / [SS] t )).

[0022] (2) Electrochemical catalytic oxidation complex breaking (S2) The treated water in step S1 enters the electrochemical reactor, using a titanium-based ruthenium-iridium anode (coating 3.5 μm, oxygen vacancies 1.2×10¹ 8 / cm³), graphite cathode, plate spacing controlled at 10-15mm, electrolyte conductivity ≥20mS / cm, current density 40mA / cm² (voltage 4.8V), simultaneous addition of K2S2O8 0.20mmol / L, reaction time 48min (t=0.8×980 / (40×A), A=electrode area 200cm²); Outlet CODCr 265mg / L (removal rate 73%), current efficiency 87% (in line with CE (%) = 100 × (1-e (-0.017×48) )=86.2%).

[0023] (3) Two-stage reverse osmosis gradient desalination (S3) The treated water in step S2 enters a two-stage reverse osmosis desalination device in series. The first-stage reverse osmosis uses an anti-pollution polyamide membrane (CODCr retention rate ≥ 95% under the standard test pressure of 0.21MPa and SDI15≤3.0), an operating pressure of 3.0MPa, a pH of 6.5-7.0, a CODCr retention rate of 96% (SDI≤3.0), and a water production flux of 22L / (m²·h); the second-stage reverse osmosis uses a polypiperazineamide seawater desalination membrane, an operating pressure of 5.1MPa, a Cl⁻ retention rate of 99.82% (membrane life L=3500×e (-0.15×5.1) =1520h, 2.4 times longer than the control ratio), water production flux 13.2L / (m²·h); Water production indicators: CODCr 28mg / L, ammonia nitrogen 2.1mg / L, TOC 8mg / L, chloride 650mg / L, TDS 1250mg / L.

[0024] (4) Low temperature MVR evaporation-crystal form control (S4) The concentrated water treated in step S3 enters the MVR treatment system, controlling the evaporation chamber to 53°C (vacuum degree -0.090MPa), the compressor compression ratio to 1:3.1, the ultrasonic anti-scaling frequency to 35kHz, the flux recovery rate η=85+15×exp(-0.6 / 1.2)=94.1%, the power density to 0.8W / L, the specific energy consumption to 23kWh / ton of water, and the output of NaCl crystals (D50 205μm, purity 99.3%, water content 0.3%); the mother liquor TDS is 208000mg / L, SO4²⁻320mg / L, and it is circulated to step S2 for treatment. The mother liquor circulation n≤log(960 / 358) / log(1.08)=2 times, and the actual circulation is 1 time (TOC increase of 8%).

[0025] Preparation of titanium-based ruthenium-iridium electrode: first, the titanium substrate was polished step by step with sandpaper to a surface roughness of Ra≤0.3μm, followed by oxalic acid etching (10wt%, boiling treatment for 2h), acetone ultrasonic cleaning (15min), vacuum dehydration (2h, 120℃, vacuum degree 10⁻³Pa) and Ar ion bombardment activation (bias -800V, time 10min); then a dual-target co-sputtering process was adopted, and the Ru target (purity ≥99.9%) and the Ir target (purity ≥99.5%) were symmetrically arranged on both sides of the substrate, the target-substrate distance was 80mm, the sputtering power was 230W (Ru target), 77W (Ir target), the Ar gas flow rate was 60sccm, the working gas pressure was 0.5Pa, and the substrate temperature was 325℃ (temperature control accuracy ±3℃); after deposition for 40min, the substrate temperature was maintained at 300℃ for annealing for 30min under Ar gas protection to form Ru 0.75 Ir 0.25 ±0.02 solid solution was obtained to obtain a titanium-based ruthenium-iridium electrode. The Ru / Ir atomic ratio was measured by EDX surface scanning to be 74.8:25.2 (deviation +0.2at%). The electrode life was measured by accelerated life test (1.5M H2SO4, 50℃, 2A / cm²) to be 6325h (the voltage increased from the initial 1.38V to 1.587V, an increase of 15.0%).

[0026] Preparation of TiO2 / nitrogen-doped graphene catalyst: Graphene oxide and nitrogen-containing precursor were first mixed in a mass ratio of 1:1.25, and hydrothermally reacted at 180°C for 12h (nitrogen protection). The product was washed with ethanol and vacuum dried at 60°C for 12h to obtain a nitrogen-doped graphene carrier with a C / N atomic ratio of 1:1.18 (XPS test), a nitrogen content of 9.2±0.3at%, and a specific surface area of ​​1023m² / g (N2 adsorption-desorption isotherm determination). TiCl4 and H2O were then used as precursors at 222 ±1℃, 56 cycles of deposition were performed, and after deposition, annealing was performed in a H2 / Ar mixed atmosphere at 400℃ for 2h to form an anatase TiO2 layer with a thickness of 2.6±0.2nm (anatase phase content ≥94.7%); then, after ultrasonic activation with 0.1M nitric acid solution for 2h, the surface was activated by heat treatment at 80℃ to make the surface hydroxyl density reach 4.8-5.2 / nm², and the carrier fluorescence lifetime was measured by time-resolved fluorescence spectroscopy (excitation wavelength 325nm) to be 15.8ns, according to GB / T 33058-2016 was used for phenol degradation experiment (10 cycles), and the TOC removal rate dropped from the initial 98.3% to 95.1%, and the BET specific surface area retention rate was 93.5%; EIS measured the interface charge transfer resistance of 48Ω·cm² (0.5M Na2SO4 electrolyte), the half-peak width of the characteristic peak of the anatase (101) crystal plane at 2θ=25.3±0.2° in the XRD spectrum was ≤0.3°, and UPS measured the heterojunction interface potential difference of 0.85eV, confirming that the prepared TiO2 / nitrogen-doped graphene catalyst has a two-dimensional layered heterojunction structure.

[0027] Example 2: This example treats shale gas fracturing flowback wastewater with an influent quality of CODCr 1500 mg / L, ammonia nitrogen 60 mg / L, TOC 1200 mg / L, chloride 23000 mg / L, and TDS 58000 mg / L, using the steps of Example 1 and adjusting some parameters: (1) Integrated coagulation and sedimentation treatment (S1): Microfiltration pretreatment with HEDP 3.0 mg / L + PESA 1.5 mg / L (mass ratio 2:1.5), flux attenuation rate 2.8% / 24h; coagulation reaction with PAC 180 mg / L, CPAM 6 mg / L (cationic degree 60%), rapid stirring 150 rpm (1 min) → slow stirring 60 rpm (12 min); after stability control with the addition of PAC 1.0 mg / L, the suspended solids dropped to 9 mg / L.

[0028] (2) Electrochemical catalytic oxidation decomposition (S2): current density 45mA / cm² (voltage 5.2V), , adding K2S2O8 0.25mmol / L, TOC removal rate is 61%.

[0029] (3) Two-stage reverse osmosis gradient desalination (S3): Secondary reverse osmosis membrane Cl⁻ / Na⁺ selectivity coefficient 1.06 (test solution NaCl 5200 mg / L); produced water TDS 1280 mg / L (in compliance with the standard).

[0030] (4) Low-temperature MVR evaporation-crystal form control (S4): The mother liquor was circulated twice (TOC increase of 9%), and the crystal sphericity was 0.86 (ImageJ analysis showed a length-to-diameter ratio of 1.1).

[0031] Example 3: This example treats shale gas fracturing flowback wastewater with an influent quality of 500 mg / L CODCr, 44 mg / L ammonia nitrogen, 760 mg / L TOC, 20000 mg / L chloride, and 50000 mg / L TDS, using the steps of Example 1 and adjusting some parameters: (1) Integrated coagulation and sedimentation treatment (S1): HEDP 2.0 mg / L + PESA 0.5 mg / L (mass ratio 2:0.5) was added during microfiltration pretreatment, and the sludge volume reduction rate was 42% (verified log([PAC]) = 0.05 × (32-28) + log(50 / 9) = 1.02, which was consistent with the logarithmic calculation of the actual dosage of 1.2 mg / L); PAC 80 mg / L and CPAM 3 mg / L (cationic degree 50%) were added during coagulation reaction, and the pH calibration frequency was once every 4 hours.

[0032] (2) Electrochemical catalytic oxidation decomposition (S2): current density 35mA / cm² (voltage 4.5V), current efficiency 85%.

[0033] (3) Two-stage reverse osmosis gradient desalination (S3): The first-stage reverse osmosis membrane has a retention rate of 98.5% for benzene series (tested for 24 hours), and the pH control response time is 28 seconds.

[0034] (4) Low-temperature MVR evaporation-crystal form control (S4): PASP with a terminal carboxyl degree of 86% and polyether-modified siloxane with an HLB value of 13 are mixed in a ratio of 4:1.5, and the mother liquor circulation flow accounts for 14% (heat transfer coefficient K = 15 × 3.1 0.8 =41W / m²·K, 35% higher than traditional evaporation).

[0035] Comparative Example: The shale gas fracturing flowback wastewater of Example 1 was treated by a conventional treatment process, including the following treatment steps: (1) Conventional coagulation and sedimentation: Add ordinary PAC (alkalinity 45%, Al2O3 20%) 200 mg / L + non-ionic PAM (molecular weight 5 million Da) 8 mg / L; single-speed stirring 80 rpm × 20 min, sedimentation tank surface load 1.2 m³ / (m²·h); effluent suspended solids ≤ 25 mg / L, no Zeta potential control measures.

[0036] (2) Activated carbon adsorption: Add 50 mg / L of coal-based activated carbon (specific surface area 600 m² / g), contact time 30 min; after adsorption, the CODCr removal rate is about 35%.

[0037] (3) Single-stage reverse osmosis: using ordinary polyamide membrane (molecular weight cutoff 150Da), operating pressure 4.0MPa; water production flux 15L / (m²·h), flux attenuation rate 12% / 24h (no antiscalant).

[0038] (4) Multi-effect evaporation crystallization: evaporation temperature 80°C (without MVR, steam thermal energy utilization rate is only 65%); output NaCl crystal purity 98.1% (sulfate impurity 0.35%), specific energy consumption 42kWh / ton water.

[0039] Compared with the comparative example, Example 1 has better treatment effect and significant advantages: in the coagulation stage, the comparative example uses inefficient PAC / PAM in the coagulation stage, has no scale inhibitor and Zeta potential regulation, and has a low suspended solids removal rate (75%), while Example 1 uses the synergistic effect of CPAM+HEDP / PESA, combined with inclined plate sedimentation + ultrasonic sludge concentration, and the suspended solids removal rate is ≥98%; the comparative example relies on activated carbon adsorption and cannot degrade complexed organic matter, resulting in an effluent CODCr removal rate of only 35%, while Example 1 uses electrocatalytic oxidation (current efficiency ≥85%) + persulfate synergistic complex breaking to greatly improve the biodegradability of wastewater; in the desalination stage, the comparative example uses a single-pole ordinary polyamide membrane (molecular weight cutoff 150Da), and high-pressure operation (4.0MPa) leads to rapid membrane pollution, and the produced water TDS exceeds the standard (2500mg / L), and the membrane life L=1200×exp (-0.22×4.0) =420h, which is only 27.6% of Example 1. In Example 1, gradient desalination (primary 2.8-3.1MPa + secondary 5.0MPa) is adopted, and antiscalant + SDI control is added to ensure membrane stability. The TDS of produced water is reduced by 50% (1250mg / L), and the membrane life is 1520h, which is 3.6 times longer than that of the comparative example. In the evaporation and crystallization stage, the energy consumption of the comparative example multi-effect evaporation is high (heat transfer coefficient K=15×1.0 0.8=15W / m²·K, 63% lower than that in Example 1), with more crystalline impurities (sulfate impurities are 0.17% higher than those in Example 1), while Example 1 adopts MVR+ultrasonic anti-scaling+crystal form regulator to achieve low energy consumption (45% energy saving compared with the comparative example) and high purity salt separation (1.2% higher than the comparative example, reaching 99.3%); at the same time, when the mother liquor TDS of the comparative example is greater than 250000mg / L, it cannot be circulated, and the cost of hazardous waste disposal increases. The mother liquor of Example 1 is circulated twice and still maintains a TOC increase of ≤10%, reducing the amount of hazardous waste by 30-40%; the comprehensive treatment cost of Example 1 is reduced by 30% compared with the comparative example.

[0040] Through comparative analysis, it can be seen that Example 1 of the present invention is significantly superior to the traditional treatment process used in the comparative example in terms of treatment efficiency (CODCr / TOC removal rate), energy consumption control (45% reduction in specific energy consumption), resource recovery (NaCl purity ≥ 99.2%) and operation stability (extended membrane life), and is particularly suitable for the treatment of shale gas fracturing flowback wastewater with TDS>50000 mg / L and containing complex organic matter, and has clear industrial application value.

[0041] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for the coordinated treatment of high-salinity organic wastewater in shale gas development, characterized in that: The following steps are involved: (1) Integrated coagulation and sedimentation treatment (S1) The high-salinity organic wastewater from shale gas development with influent CODCr 1000±500mg / L, ammonia nitrogen 52±8mg / L, TOC 980±220mg / L, chloride 21580±1500mg / L, TDS 54280±4000mg / L was treated in the following order: ① Microfiltration pretreatment: using α-Al2O3 ceramic microfiltration membrane (pore size 0.20-0.25μm), controlling the transmembrane pressure difference to 0.18-0.22MPa, membrane surface flow rate to 3.0-3.5m / s, synchronously adding HEDP 2.0-3.0mg / L and PESA 0.5-1.5mg / L (mass ratio 2:1±0.3), scale inhibition efficiency ≥90% (CaCO3 scaling rate ≤0.05g / (m²·h)); ② Coagulation reaction: add PAC 50-300mg / L, CPAM 2-15mg / L (cationic degree ≥50%, intrinsic viscosity ≥4.0dL / g), stir at gradient speed in stages (paddle diameter / pool diameter ratio 1:3-1:5, G value control of 400-600 s⁻¹ in fast stage, corresponding speed 120-150 rpm, reaction time 2±1min, G value control of 30-50 s⁻¹ in slow stage, corresponding speed 40-60 rpm, reaction time 15±5min), adjust pH to 6.5-7.0 (0.5mol / L NaHCO3 linkage control, response time ≤20s); ③ Inclined plate sedimentation: using reinforced polypropylene inclined plate (inclination angle 55-60°, bending strength ≥ 60MPa), surface load ≤ 0.8m³ / (m²·h), supporting ultrasonic sludge concentration (28±2kHz, power density 0.6-0.8W / L), sludge moisture content is reduced from 99% to 95-97%; ④ Stability control: When |Zeta potential| < 30mV, automatically add PAC 0.5-1.0mg / L (Al2O3 ≥ 28%) and start alkaline washing (0.1mol / L NaOH 30s → water washing 20s) to make the suspended solids in the effluent ≤ 10mg / L and |Zeta potential| ≥ 30mV; (2) Electrochemical catalytic oxidation complex breaking (S2) The treated water in step S1 enters the electrochemical reactor and uses a titanium-based ruthenium-iridium anode (coating 3.2-3.8μm (uniformity ≤±5%), oxygen vacancies ≥1×10¹ 8 / cm³) and graphite cathode, control the current density to 35-45mA / cm² (voltage to 4.5-5.2V), plate spacing to 7±0.5mm, flow rate to 1.0±0.1m / s, time to 45-50min, and simultaneously add K2S2O8 0.15-0.25mmol / L (increase by 0.05mmol / L / time during mother liquor circulation), so that CODCr removal rate ≥70%, TOC ≥60% (current efficiency ≥85%); (3) Two-stage reverse osmosis gradient desalination (S3) The treated water in step S2 enters a two-stage reverse osmosis desalination device in series. The first-stage reverse osmosis adopts an anti-pollution polyamide membrane (molecular weight cutoff 280±20Da), an operating pressure of 2.8-3.1MPa, a pH of 6.5-7.0, a CODCr retention rate ≥95% (SDI≤3.0), and a water production flux ≥20L / (m²·h); the second-stage reverse osmosis adopts a polypiperazineamide seawater desalination membrane (operating pressure 5.0±0.2MPa), a Cl⁻ retention rate ≥99.8%, and a water production flux of 0.60±0.03 times that of the first stage; Water production indicators: CODCr<35mg / L, ammonia nitrogen<2.5mg / L, TOC<10mg / L, chloride<700mg / L, TDS<1300mg / L (in compliance with DB51 / 3203-2024); (4) Low temperature MVR evaporation-crystal form control (S4) In step S3, the concentrated water enters the MVR treatment system, controls the evaporation chamber to 50-55°C (vacuum degree -0.090±0.002MPa), the compressor compression ratio to 1:3.1±0.05 (specific energy consumption ≤25kWh / ton of water), ultrasonic anti-scaling (35±1kHz, power density 0.8±0.1W / L), and produces NaCl crystals (D50 200±10μm, purity ≥99.2%, water content ≤0.4%); when the mother liquor TDS ≤210000mg / L and SO4²⁻ ≤350mg / L, circulate to S2 for treatment (cycle ≤2 times, TOC increase ≤10%).

2. The method for co-processing high-salt organic wastewater in shale gas development according to claim 1, characterized in that: In the step S1, the microfiltration membrane flux attenuation rate is ≤3% / 24h (chemical cleaning cycle is ≥72h), the coagulation pH fluctuation is ≤±0.2 (calibration frequency is ≥1 time / 4h), and the sludge volume reduction rate is ≥40%.

3. The method for co-processing high-salt organic wastewater in shale gas development according to claim 1, characterized in that: In step S2, the titanium-based ruthenium-iridium electrode is prepared by magnetron sputtering, with a sputtering power of 200-250W, Ar 50-80sccm, a substrate temperature of 300-350°C, a Ru / Ir molar ratio of 7.5:2.5±0.2 (composition deviation ≤±0.3at%), and an accelerated life of ≥6200h (a cell voltage increase of ≥15% is a failure standard).

4. The method for co-processing high-salt organic wastewater in shale gas development according to claim 1, characterized in that: In step S3, the first-level membrane has a retention rate of ≥98% for benzene series (tested for 24 hours), the second-level membrane has a Cl⁻ / Na⁺ selectivity coefficient of ≥1.05 (NaCl 5000±200 mg / L), and the pH control response is ≤30s (calibration frequency ≥1 time / 8 hours).

5. The method for co-processing high-salt organic wastewater in shale gas development according to claim 1, characterized in that: In the step S4, PASP (terminal carboxyl group ≥ 85%) is compounded with polyether-modified siloxane (4:1±0.5), the crystal sphericity is ≥ 0.85 (100 samples were analyzed by ImageJ), and the mother liquor circulation flow rate accounts for ≤ 15%.

6. The method for co-processing high-salinity organic wastewater in shale gas development according to claim 1, characterized in that: The preparation of the TiO2 / nitrogen-doped graphene catalyst in step S2 includes: hydrothermal synthesis of nitrogen-doped graphene carrier (C / N 1:1.1-1.3, nitrogen content 7.5-10.5at%, specific surface area 900-1100m² / g); ALD deposition of TiO2 (220±5°C, 55-58 cycles), thickness 2-3nm (anatase phase ≥93%); catalyst surface hydroxyl density 4.8-5.2 / nm², fluorescence lifetime ≥15ns; TOC removal rate decay ≤5% (specific surface area loss ≤8%) after 10 cycles; the catalyst has a two-dimensional layered heterojunction (interface charge transfer resistance ≤50Ω·cm²), XRD 2θ=25.3±0.2° (half peak width ≤0.3°).

Citation Information

Patent Citations

  • Method for synthesizing titanium dioxide / graphene nano composite material

    CN105903462A

  • Spherical calcite calcium carbonate crystal preparation method

    CN107285361A

  • Method for zero-discharging treatment of ternary material cleaning wastewater

    CN109574356A

  • Advanced treatment process for shale gas fracturing flow-back fluid and produced water

    CN113830956A

  • Method for treating antibiotic wastewater by electrochemically activating peroxymonosulfate

    CN114715982A

Cited By

  • Fluorine-containing high-salinity wastewater treatment system and process

    CN121158991A